APLIKASI INTELLIGENCE WEBSITE UNTUK PENUNJANG LAPORAN PAUD PADA HIMPAUDI KOTA TANGERANG - Dina Fitria Murad; Nia Kusniawati; Agus Asyanto (CCIT Journal, 2013)
The development of technology has affected all the human life as well in education aspect. The computer device usage become usual to be applied in education, especially in managing student data for report making. Like any organization, HIMPAUDI Kota Tangerang strives to realize the computer application using to evaluating regular reports of PAUD, early childhood education institutions in each month. The report which written manually by paper media has created many obstacles in the process of recapitulation of the whole report by HIMPAUDI. Furthermore, the problem of the delaying PAUD report caused by the location of PAUD which spread across Tangerang. HIMPAUDI districts subdivision tasked to collect regular reports on each district and give it to HIMPAUDI. These activities take much time so the collection of regular monthly reports being late. With these problems, the authors conducted an analysis to find solutions to these problems using waterfall method by creating a HIMPAUDI website that can be used by PAUD to send their report easily. PAUD administrator easily access the website for report delivery in excel file format, that can be directly sent to HIMPAUDI website and automatically recapitulated in to graphical form which receivedby HIMPAUDI. In addition, the HIMPAUDI can choose parameters such graphs are shown by year, age, study groups, etc.. So the monitoring process of report distribution and recapitulation will automatically processed by the system with good performance, well integrated, reduces error rate, saving time and cost, and help HIMPAUDI to monitor the development of PAUD easily